Three main stressors acting on the Ria Formosa lagoonal system (Southern Portugal): physical stress, organic matter pollution and the land–ocean gradient - Gamito, Sofia (2013)
During the last 15 years of the 20th century, several researchers carried out extensive sampling of benthic macrofauna communities in the Ria Formosa lagoon. The main objective of this paper is to discern the main communities of benthic fauna of the Ria Formosa and the leading stressors that limit them based on this large data set. The high species richness and high diversity values observed at most of the stations or groups of stations indicate a good ecological status, with the exception of the sewage-impacted areas and the physically stressed areas. It was possible to define three main stressors acting on the Ria Formosa. The most important is the physical stress imposed by the limited water renewal in some areas of the Ria Formosa. The second is the nutrient and organic matter pollution that is limited to the vicinity of the sewage outfall stations and to some locations of the Ria Formosa. This is due to the dual effects of the low residence time of water, but also due to a degradation of water quality in places of relatively restricted water circulation but with high primary production, symptoms of eutrophication. The third stressor is the natural land-ocean gradient, denoting the influence of seawater exchanges and emersion time, attenuated by the high water exchange rates of Ria Formosa. It was possible to differentiate the anthropogenic stress from the natural physical stress through the application of multivariate analysis. However, both structural (species richness and diversity indices) and functional indicators (trophic composition) indicate the same trend - low species richness, low diversity indices, and a community dominated by detritivores species at the locations characterized by high anthropogenic impact or by physical stress. The physically stressed areas were dominated by chironomid larvae and hydrobiid gastropods and the most polluted areas were dominated by oligochaetes, mainly tubificids.